2016
DOI: 10.1093/toxsci/kfw014
|View full text |Cite
|
Sign up to set email alerts
|

PBPK Model for Atrazine and Its Chlorotriazine Metabolites in Rat and Human

Abstract: The previously-published physiologically based pharmacokinetic model for atrazine (ATZ), deisopropylatrazine (DIA), deethylatrazine (DEA), and diaminochlorotriazine (DACT), which collectively comprise the total chlorotriazines (TCT) as represented in this study, was modified to allow for scaling to humans. Changes included replacing the fixed dose-dependent oral uptake rates with a method that represented delayed absorption observed in rats administered ATZ as a bolus dose suspended in a methylcellulose vehicl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…Exposure was determined by using TCT chemographs along with daily surveys of individual human water consumption ( Barraj et al , 2009 ). The resulting temporal pattern of human exposure was converted to estimated, time-dependent, internal human plasma TCT concentrations using a PBPK model ( Campbell et al , 2016 ). The human POD was established by using the PBPK model to convert an administered TCT-POD dose to the TCT-POD plasma concentration ( Figure 1 ).…”
mentioning
confidence: 99%
“…Exposure was determined by using TCT chemographs along with daily surveys of individual human water consumption ( Barraj et al , 2009 ). The resulting temporal pattern of human exposure was converted to estimated, time-dependent, internal human plasma TCT concentrations using a PBPK model ( Campbell et al , 2016 ). The human POD was established by using the PBPK model to convert an administered TCT-POD dose to the TCT-POD plasma concentration ( Figure 1 ).…”
mentioning
confidence: 99%
“…The tolerance of maize to chlorotriazines has been linked to higher levels of expression and activity of GST (Timmerman, 1989) and that when weeds develop resistance to ATR, it is often attributed to increased expression/activity of GST in the resistant weed (Anderson & Gronwald, 1991;Evans et al, 2017). In a pharmacokinetic model of ATR (Campbell et al, 2016), it has been demonstrated that the clearance of chlorotriazines from plasma was most sensitive to the rate of elimination of the ATR metabolite, DACT (Breckenridge et al, 2016). Thus, the rate of the clearance of ATR and its metabolites from plasma is directly dependent on GSH levels and GST expression and activity in the liver and kidney.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, ATR is rapidly absorbed, dealkylated in the liver by CYP P450 liver enzymes (Lang et al, 1996) and eliminated in urine and feces, predominantly as glutathione (GSH) conjugated chlorotriazine mercapturates. ATR has a terminal half-life of elimination of approximately 31 h in humans (Campbell et al, 2016) and plasma clearances of 2.4, 6.9, 6.0 and 8.1 h for ATR and its three chlorotriazine (DEA, DIA and DACT) metabolites, respectively, in female rats administered ATR by gavage (McMullin et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Human exposure to atrazine or terbuthylazine results in a relatively fast urinary excretion of the parent compounds and their dealkylated and conjugated metabolites (104,105). The half-life of atrazine, for example, is only 24-31 h (106,107). The parent compound is, therefore, generally detected only in minor amounts in the urine, usually after continuous occupational exposure.…”
Section: Epidemiological Studiesmentioning
confidence: 99%